INTERACTIVE EFFECT OF WORK PLACE SPIRITUALITY AND JOB AUTONOMY WITH ORGANIZATIONAL BASED SELF -ESTEEM ON ORGANIZATIONAL LEARNING CULTURE - Hussain, Mansoor; Gulzar, Amir (International Journal of Psychosocial Rehabilitation, 2020)
Learning has assumed added significance over the period of time and considered as key factor to the success of organizations. There is an ongoing debate among academics and practitioners alike about real essence of learning and its determinants. In this study the main purpose is to examine the role of organizational based self-esteem as one enabler of organizational learning culture. A model has been proposed to scientifically analyze the moderating effects of work place spirituality and job autonomy between organizational based self- esteem and organizational learning culture. Employees from private security companies participated in this research and linear regression analyses along PROCESS MACRO executed in SPSS are used to test hypotheses. This research positions work place spirituality and job autonomy in learning culture debate and implies that learning can be enriched by attending to spiritual enrichment and autonomous jobs. The research suggests a significant relationship between organizational based self – esteem and organizational learning culture, whereas moderation by work place spirituality is not proven.